Nível de atividade física e fatores associados: um estudo com trabalhadores do setor metal-mecânico do município de Ponta Grossa/PR - Vargas, Leandro Martinez (2011)
This study aims to estimate of the level of physical activity in the population of adult workers in the metal-mechanic sector of the city of Ponta Grossa, Parana, Brazil, and associated factors. Was conducted a population-based cross-sectional study, with individuals of both genders, between 18 and 65 years of age (n = 298). To this end, we used the International Physical Activity Questionnaire (IPAQ), in the short form, and the cutoff of 150 minutes of weekly physical activity to differentiate between active and inactive individuals. Examined factors associated were socio-demographic (gender, age, marital status, education and family income), labor (occupational class) and perception of health. We performed descriptive analysis, dependency between variables (chi-square, p ≤ 0.05) and binary logistic regression analysis. The prevalence of inactivity of the total sample was 29.9% (95% CI: 24.7 to 35.4).Separating by gender and occupation, women and individuals in administrative and senior executive level were more sedentary, 43.3% (95% CI: 25.4 to 62.5) and 36.7% (95%: 27 0.6-46 .4), respectively. The variables occupation, age and family income showed positive association with physical activity level. Physical activity was more prevalent in factory floor workers and general services, of individuals aged 18-29 and 50-68 years and among the poor. The prevalence of physically active workers is high and follows similar patterns to other cities and regions of the country and the socio-demographic variables associated with physical activity. Because this prevalence may be influenced by occupational and domestic physical activity, interventions through the creation of public spaces focused on health promotion and increased leisure physical activity at work, are solutions to increase the level of workers total physical activity.